IMPLEMENTASI KOMPETENSI PEDAGOGIK GURU SD NEGERI 2 KUALA BARU ACEH SINGKIL - Nurhaidah Nurhaidah. (Universitas Syiah Kuala, 2019)
Pendidikan Guru Sekolah Dasar JURNAL PESONA DASARUniversitas Syiah Kuala Vol.7 No.1, April 2019, hal.67 – 76 ISSN: 2337-9227NurhaThis study, entitled implementation of the competence of Pedagogic Teacher SD Negeri 2Kuala Baru Aceh Singkil. This research aims to know the Pedagogy Teacher SD Negeri 2New Aceh Singkil Kuala. The approach used in this study is qualitative and descriptiveresearch types. Subjects in the study were 14 teachers in SD Negeri Kuala Baru Aceh Singkil.Data collection is done by observation techniques. All data processed with the next stage ofthe analysis the qualitative data, namely data reduction, data model (Data Display), andwithdrawal/verification conclusion. Data that have been obtained are then analyzed usingdescriptive percentage formula. The results of this research show that the implementation ofthe competency of the Pedagogy in SD Negeri 2 Kuala Baru Aceh Singkil already belongs,although there are some constraints experienced by the teachers. It is seen from thecompetence on aspects of the planning, execution and control of learning. Less teacher planwell the learning activities will be undertaken and methods/approaches to learning that areused are conventional teacher. Pedagogic competence is the ability of teachers in managinglearning learners, and a teacher of skills related to the study of the interaction betweenteacher and student which includes an understanding of learners as an understanding of thenature, characteristics, and development of children in the process of teaching and learningin terms of providing material or evaluations in order to actualize the various potentiallearners. 76